2021
DOI: 10.1177/2277975220975513
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotypes and Their Impact on Women’s Career Progressions from a Managerial Perspective

Abstract: Gender stereotypes continue to exist and are transmitted through media, and through social, educational and recreational socialization, which promote gender prejudice and discrimination. This paper argues that contemporary management culture does not critically engage with the social theories of gender studies, which could help in developing gender-neutral affirmative action-oriented managerial perspectives. The paper outlines different aspects of gender stereotyping and their impact on women’s career progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
87
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 132 publications
(220 reference statements)
2
87
0
5
Order By: Relevance
“…Kemya from Iran, (BSc Public health) 21 years old "Unfortunately, we are facing a lot of genders stereotyping in our society". This result is corresponding with the research hypothesis, the higher educated societies, the higher educated females and the results of (Fagot et al, 1992;Tabassum & Nayak, 2021).…”
Section: Gender Stereotyping Factorssupporting
confidence: 89%
See 1 more Smart Citation
“…Kemya from Iran, (BSc Public health) 21 years old "Unfortunately, we are facing a lot of genders stereotyping in our society". This result is corresponding with the research hypothesis, the higher educated societies, the higher educated females and the results of (Fagot et al, 1992;Tabassum & Nayak, 2021).…”
Section: Gender Stereotyping Factorssupporting
confidence: 89%
“…Fagot, Leinbach, and O'Boyle (1992) points out that gender awareness is acquired at a young age and that gender identity is heavily influenced by social interactions with the situation. Tabassum and Nayak (2021). concluded that the development of a child's personality occurs primarily in the family environment but is strongly influenced by social factors.…”
mentioning
confidence: 99%
“…According to these stereotypes, males, due to psychological predispositions, are a better fit for managerial positions. As such stereotypes still exist, 71,72 our findings argue for the implementation of organizational policies based on sex equality. Such policies would increase the upward potential of employees, minimize feelings of injustice, and positively influence staff morale.…”
mentioning
confidence: 81%
“…There have been countless studies of men and women in management positions and people's perceptions of their performance. [2] The same behaviors of men and women are often interpreted differently because the observers paste different labels of the same behaviors performed by men and women. One reason for this is sexual fantasies.…”
Section: Introductionmentioning
confidence: 99%